In vitro and in vivo synergistic inhibition of Malassezia furfur targeting cell membranes by Rosa rugosa Thunb. and Coptidis Rhizoma extracts - Li, Li; He, Yuanyuan; Zou, Qinghui; Chen, Weiwei; Liu, Yanxia; He, Huifen; Zhang, Jun (Frontiers in Microbiology, 2024)
Malassezia furfur (M. furfur) is a significant pathogen responsible for various dermatological conditions, adversely affecting the quality of life. This study aims to evaluate the phytochemical composition by high-performance liquid chromatography (HPLC) and the synergistic antifungal effects of a combined extract of Rosa rugosa Thunb. (MG) and Coptidis Rhizoma (HL) against M. furfur in vitro and in vivo. The major compounds identified include gallic acid, rutin, isoquercitrin, palmatine, epiberberine, berberine hydrochloride, and coptisine. The checkerboard and time-kill assays revealed that Meilian extract (ML, containing crude drug concentration of 3.125 mg/mL MG and 6.25 mg/mL HL) exhibited synergistic antifungal activity against M. furfur. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) revealed damage to the fungal surface, mitochondrial swelling, and cell membrane disruption after treatment. Propidium iodide staining, protein concentration assays, and ergosterol quantification experiments indicated that the ML compromised the integrity of M. furfur's cell membrane, leading to leakage of cellular contents. Transcriptomic analysis identified 131, 275, and 293 differentially expressed genes in M. furfur exposed to MG, HL, and ML, respectively, with significant enrichment in membrane function related pathways, amino acid metabolism, carbohydrate metabolism, and energy metabolism, causing membrane dysfunction. Moreover, in a seborrheic dermatitis mouse model induced by M. furfur, the ML demonstrated synergistic antifungal effects and alleviated skin inflammation. These findings suggest that the synergistic antifungal effect of the combined MG and HL might be associated with cell membrane disruption, metabolic disturbance. This study provides a theoretical basis for understanding the antifungal mechanisms of the ML.